CO2 methanation over Ni and Rh based catalysts: Process optimization at moderate temperature. (26th April 2018) - Younas, Muhammad; Sethupathi, Sumathi; Kong, Leong Loong; Mohamed, Abdul Rahman
Summary: H2 was produced from aluminum/water reaction and reacted with CO2 over Ni and Rh based catalysts to optimize the process conditions for CO2 methanation at moderate temperature. Monometallic catalysts were prepared by incorporating Ni and Rh using nickel nitrate hexahydrate (Ni(NO3 )2 ·6H2 O) and rhodium(III) chloride trihydrate (RhCl3 ·3H2 O)as a precursor chemical. The preliminary study of the catalysts revealed higher activity and CH4 selectivity for Rh based catalyst compared to that of Ni based catalyst. Further, Rh based catalyst was investigated using response surface methodology (RSM) involving central composite design. The quadratic model was employed to correlate the effects of variable parameters including methanation temperature, %humidity, and catalyst weight with the %CO2 conversion, %CH4 selectivity, and CH4 production capacity. Analysis of variance revealed that methanation temperature and humidity play an important role in CO2 methanation. Higher response values of CO2 conversion (54.4%), CH4 selectivity (73.5%) and CH4 production capacity (8.4 μmol g −1  min −1 ) were noted at optimum conditions of 206.7°C of methanation temperature, 12.5% humidity and 100 mg of the catalyst. The results demonstrated the ability of Rh catalyst supported on palm shell activated carbon (PSAC) for CO2 methanation at low temperature and atmospheric pressure.